Free facilities or false promises? The effects of Accredited Social Health Activists' home visits on maternal and newborn health equity in Uttar Pradesh, India: a mixed methods study. (March 2019) - Blanchard, Andrea; Ansari, Shahnaz; Rajput, Rajni; Das, Arup Kumar; Houweling, Tanja; Colbourn, Timothy; Prost, Audrey
Abstract: Background: The state of Uttar Pradesh has one of the highest neonatal mortality rates in India (45 per 1000 livebirths), with substantially more deaths among the poorest people. To address this, India's National Health Mission has trained community-based incentivised volunteers called Accredited Social Health Activists (ASHAs) to visit all pregnant women at home and support them to deliver their babies in public hospitals or clinics. Contextual processes greatly shape community-based efforts to reduce health inequities, yet few studies have examined these dynamics. We undertook a mixed methods study to understand the extent to which, how, and in what circumstances ASHAs' home visits reduce gaps between socioeconomic groups in institutional delivery rates in Uttar Pradesh, India. Methods: We conducted generalised linear modelling using a cross-sectional survey in a representative random sample of women who had given birth within the last 2 months in 25 districts in 2014–15. We conducted qualitative social mapping and focus group discussions in four villages that were more and less remote in two districts, with purposively selected ASHAs, and mothers from higher and lower socioeconomic groups (n=134). We used thematic framework analysis. Sigma Institutional Review Board and University College London Research Ethics Committee provided ethics approval. Findings: We included data from 57 778 women. Institutional delivery rates were 7 and 12 percentage points more equal between the highest and lowest caste (RR 1·09 [95% CI 1·04–1·14] vs 1·25 [1·17–1·33]) and education groups (1·29 [1·26 −1·31] vs 1·66 [1·61–1·70]), respectively, in women who received any third trimester home visits from ASHAs compared with no visit. The qualitative data showed that ASHAs' promotion of incentives and free care influenced families of lower socioeconomic position to deliver their babies in public community health centres. However, many of these families lost faith in the facilities when they experienced indirect costs, lack of medicines or transport, and poor treatment, particularly in the remote villages. These issues also led complicated deliveries to be referred to higher-level, often private, hospitals that poor families can ill afford, and wealthier families to opt directly for private care. Interpretation: This study provides guidance for adapting implementation strategies within socioeconomic and health system contexts by strategically supporting ASHAs to build relationships with all families, eliminating indirect costs and other accessibility barriers, and strengthening the quality of care at public health facilities where most needed. This would help alleviate families' widespread reliance on emergency and expensive delivery care, and reinforce ASHAs' role in improving maternal and newborn health equity. Funding: None.